Facilitating an Elementary School-Wide Immersive Academic Event - Kinskey, Melanie; Ruzek, Mitch; Zeidler, Dana L. (Innovations in Science Teacher Education, 2021)
Traditional science teaching has tended to focus on compartmentalized academic content that is removed from the practice of everyday life. Confronting this has been a perennial challenge in science teacher education, and the impact on the stifling of students’ creativity, critical thinking, and engagement has been well documented in the literature. Progressive science teaching, however, emphasizes situating instruction in sociocultural contexts that engage children in the activity of learning by tapping into their natural instincts of wonder, curiosity, questioning, and actively seeking meaning about the world around them. This article describes week-long, immersive, inquiry-based events that university educators facilitate at local schools. The purpose of the events is to model how to engage students in inquiry-based experiences and stimulate their natural curiosity and, at the same time, facilitate professional development for teachers. These educative experiences are positioned in the notion of interdisciplinary, inquiry-based learning that drew from science, the creative arts, social sciences, language arts, and mathematics. During this week-long event, we build a community of engagement aimed at fostering heightened levels of academic commitment, developing natural inquiry skills, and cultivating authentic scientific habits of mind through inquiry that would captivate both students and teachers across multiple grade levels.